Fraud Hexagon Theory dalam Mendeteksi Financial Statement Fraud Pada Perusahaan Sektor Healthcare yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2019 - 2023 - Wilda Ariza, Asti Nur; Versiandika Yudha Pratama (Journal Of Islamic Economics And Finance, 2025)
This study examines fraudulent financial reporting in healthcare companies listed on the Indonesia Sharia Stock Index (ISSI) using Vousinas’ Fraud Hexagon Theory, which includes six factors: stimulus, opportunity, rationalization, capability, ego, and collusion. Using a quantitative approach with purposive sampling, 13 healthcare companies during 2019–2023 were analyzed through multiple linear regression with SPSS. The results reveal that CEO’s Picture (ego) and State-Owned Enterprise (collusion) significantly influence financial statement fraud, while other variables show no significant effect. Collectively, all independent variables affect fraudulent reporting. These findings enrich empirical evidence of the Fraud Hexagon Theory in sharia-based healthcare firms and offer practical insights to strengthen governance and fraud prevention in Islamic financial reporting.